Economy Today (Wydawnictwo Uniwersytetu Łódzkiego, 2026)
The book fits into a multidisciplinary research approach. The articles are the result of research conducted by eminent international economists, authors representing academic centres in different countries. The articles address current phenomena observed in the global economy. The authors do not aspire to comprehensively explain all the very complex and multi-dimensional economic developments, but illustrate many of these phenomena in an original way. The multi-threaded and multi-dimensional nature of the discussion in particular articles deserves attention. These include theoretical and methodological articles as well as the results of empirical research presented by the authors. The book is addressed to those persons interested in issues of economics, finance, regional economy, and the management sciences. lt can be valuable for economic practitioners, members of management and supervisory boards of companies, and financial analysts, and the articles may also be useful for academicians and students.